The Determinants of Born Global Companies Emergence in Central European Countries - Elena Pawęta (Entrepreneurial Business and Economics Review, 2013)
The  purpose  of  this  paper  is  to  review  potential  determinants  of  born global  companies  emergence  in  Central  Europe  (CE)  through  the  example  of  the Visegrad Group countries.